2019
DOI: 10.1093/cid/ciz1171
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in Elderly Persons According to the Year of Diagnosis of Human Immunodeficiency Virus Infection: A Cross-sectional Dat’AIDS Cohort Study

Abstract: Background We assessed prevalence of multimorbidity (MM) according to year of human immunodeficiency virus (HIV) diagnosis in elderly people living with HIV (PLWH). Methods This was a cross-sectional study of MM in PLWH aged ≥70 years from the Dat’AIDS French multicenter cohort. MM was defined as at least 3 coexistent morbidities of high blood pressure, diabetes mellitus, osteoporosis, non-AIDS cancer, chronic renal failure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
2
5
0
1
Order By: Relevance
“…Significant changes in the immune profile were detected, with a remarkable improvement of CD4 + T cells count, CD8 + T cells count and CD4 + /CD8 + ratio among both the overall population and over 55 PLWH. Our observations that confirm a positive effect of BIC/FTC/TAF among elderly PLWH is reassuring, considering that aging is known to be accompanied by immune senescence, with the CD4 + /CD8 + ratio being a strong indicator of frailty and multi-morbidity [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 56%
“…Significant changes in the immune profile were detected, with a remarkable improvement of CD4 + T cells count, CD8 + T cells count and CD4 + /CD8 + ratio among both the overall population and over 55 PLWH. Our observations that confirm a positive effect of BIC/FTC/TAF among elderly PLWH is reassuring, considering that aging is known to be accompanied by immune senescence, with the CD4 + /CD8 + ratio being a strong indicator of frailty and multi-morbidity [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 56%
“…Several studies confirmed that achieving CD4 counts ≥500 cells/µL was associated with a lower mortality [29,35]. Although few studies investigated the association between CD4/CD8 ratio restoration ≥0.8 and mortality, Demontès M, et al [36] reported multimorbidity was associated with CD4/CD8 ratio < 0.8, and Marianna M, et al [37] found CD4/CD8 ratio < 0.8 could be used as a predictor for cardiovascular diseases. This new system could have several important implications in clinical practice: (1)it could guide physicians, healthcare providers, and social workers to accurately assess the immune status upon ART, and retarget those patients who were considered to have achieved immune restoration based on normalized CD4 counts alone, (2) in the era of "treat all", using CD4 cell counts as the only immune evaluation parameter may lead to the overestimation of successful immune restoration and neglection of the risk of death in patients with HIV, (3) the high probability of incomplete immune reconstitution after long-term treatment implies that only ART might not be sufficient to achieve complete immune restoration.…”
Section: Discussionmentioning
confidence: 96%
“…O HIV, junto à imunodefi ciência crônica e ativação imune, está envolvido no envelhecimento acelerado. Ainda, as primeiras gerações de terapia antirretroviral também estão associadas à incidência de algumas comorbidades, principalmente às síndromes metabólicas e cardiovasculares 18 . Há também uma alta prevalência de riscos comportamentais nas PVHIV, como o tabagismo e uso recreativo de drogas, os quais estão associados a muitas comorbidades 19, 20 .…”
Section: Tabelaunclassified